Apakah Corporate Governance ikut Mempengaruhi Tingkat Underpricing Perusahaan? - ANDI AMRI; RAMADHI RAMADHI (Universitas Negeri Padang, 2021)
Companies that have the potential will continue to improve by making innovations, being creative and innovating. So that it is expected to obtain qualified funding. This qualified funding will certainly be referred to by looking at the corporate governance structure and the level of underpricing for companies conducting Initial Public Offering (IPO). In achieving the company's goals, many theories put forward by experts. One of them is signaling theory. This theory explains that the existence of a good corporate governance structure, when a company conducts an IPO. This is a positive signal for investors to get involved in a company. Important points in corporate governance include the number of commissioners, dependent commissioners, ownership concentration and institutional ownership. The method used is comparative causal research using multiple regression analysis. Sample 62 observations in companies that have IPO from 2011 to 2016. The results show the number of members of the board of commissioners, the level of independence of the board of commissioners has a significant effect on underpricing. however, the concentration of ownership and institutional ownership has no significant effect on underpricing.